Development and validation of a correction equation for Corvis tonometry. Issue 9 (3rd July 2016) - Joda, Akram Abdelazim; Shervin, Mir Mohi Sefat; Kook, Daniel; Elsheikh, Ahmed
Abstract: Primary objective: This study uses numerical analysis and validation against clinical data to develop a method to correct intraocular pressure (IOP) measurements obtained using the Corvis Tonometer for the effects of central corneal thickness (CCT), and age. Materials and Methods: Finite element analysis was conducted to simulate the effect of tonometric air pressure on the intact eye globe. The analyses considered eyes with wide variations in IOP (10–30 mm Hg), CCT (445–645 microns), R (7.2–8.4 mm), shape factor, P (0.6–1) and age (30–90 years). In each case, corneal deformation was predicted and used to estimate the IOP measurement by Corvis (CVS-IOP). Analysis of the results led to an algorithm relating estimates of true IOP as a function of CVS-IOP, CCT and age. All other parameters had negligible effect on CVS-IOP and have therefore been omitted from the algorithm. Predictions of corrected CVS-IOP, as obtained by applying the algorithm to a clinical data-set involving 634 eyes, were assessed for their association with the cornea stiffness parameters; CCT and age. Results: Analysis of CVS-IOP measurements within the 634-large clinical data-set showed strong correlation with CCT (3.06 mm Hg/100 microns, r 2  = 0.204) and weaker correlation with age (0.24 mm Hg/decade, r 2  = 0.009). Applying the algorithm to IOP measurements resulted in IOP estimations that became less correlated with both CCT (0.04 mm Hg/100 microns, r 2  = 0.005) and age (0.09 mm Hg/decade, r 2  = 0.002). Conclusions: The IOP correction process developed in this study was successful in reducing reliance of IOP measurements on both corneal thickness and age in a healthy European population.